Lean thinking contributions for Industry 4.0: a systematic literature review - Bittencourt, V. L. (2019)
Lean Thinking has successfully challenged mass production practices, providing greater flexibility in production systems and processes, resulting in "leaner" products and supply chains, i.e., with less waste. More recently, the term Industry 4.0 emerged. It was first used in Germany in 2011 to refer to the 4th industrial revolution. It aims to connect the physical and virtual worlds in industrial production and has become increasingly popular with the many opportunities and business models that can be consolidated through new technologies. With such automation associated with Industry 4.0, questions arise about the interoperability between the two approaches and the role of Lean in this ongoing industrial revolution. Therefore, a systematic literature review was carried out in order to answer the research questions, and to identify the role of Lean in this scenario. The review was conducted for the period from 2011 to 2018 and resulted in a total of 26 articles being analyzed. This paper's focus is the effect of Lean Thinking as a facilitator, within the scope of Industry 4.0. It is also clear that this is an emerging research area, with most of the selected studies published between 2017 and 2018. (C) 2019, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.